Efficacy of intravenous propranolol for life‐threatening diffuse neonatal hemangiomatosis. Issue 4 (16th May 2022) - Ishikawa, Takamichi; Seki, Keigo; Uchiyama, Hiroki
Abstract: Oral propranolol is recommended as the first‐line agent for infantile hemangioma requiring systemic treatment. Life‐threatening complications such as obstructive infantile hemangioma of the airway or infantile hepatic hemangioma associated with high‐output congestive heart failure are major indications for the consideration of early treatment. We present the case of an infant with life‐threatening diffuse neonatal hemangiomatosis, including airway obstruction due to subglottic hemangioma, heart failure due to multiple hepatic hemangiomas with portohepatic venous shunts, and severe anemia due to continuous gastrointestinal bleeding, in which treatment with intravenous propranolol proved successful.